Minimally Invasive Pouch Roll Technique to Augment Peri‐Implant Soft Tissue With an 810‐nm Photoablative Diode Laser: Report of Three Cases. Issue 3 (3rd July 2018) - Giannelli, Marco; Lorenzini, Luca; Bani, Daniele
Abstract : Introduction: Second‐stage surgery for dental implant uncovering offers an opportunity to surgically correct ridge deficiencies in esthetic areas, or simply to enhance thickness of the marginal gingiva for a more stable interface with the implant. This case report illustrates an alternative laser‐aided approach to perform peri‐implant soft tissue augmentation by the pouch roll technique. Case Presentation: Five implants in three patients with a mild horizontal ridge deficiency and minimal keratinized marginal gingiva were corrected at the time of implant uncovering using a λ 810‐nm photoablative diode laser for atraumatic selective de‐epithelialization and soft tissues incision, featuring minimal surgical trauma and patients' discomfort. Conclusion: Within the limitation of the small number of patients, the described method for correction of mild buccal ridge deficiencies allowed fast healing, satisfactory clinical and esthetic results, rapid prosthetic restoration and no need for local or systemic analgesics, with obvious advantages for the patients.